Diclofenac Administration after Physical Training Blunts Adaptations of Peripheral Systems and Leads to Losses in Exercise Performance: In Vivo and In Silico Analyses - Rômulo Pillon Barcelos; Frederico Diniz Lima; Aline Alves Courtes; Ingrid Kich da Silva; Jose Eduardo Vargas; Luiz Fernando Freire Royes; Cristiano Trindade; Javier González-Gallego; Félix Alexandre Antunes Soares (MDPI AG, 2021)
Recovery in athletes is hampered by soreness and fatigue. Consequently, nonsteroidal anti-inflammatory drugs are used as an effective strategy to maintain high performance. However, impact of these drugs on adaptations induced by training remains unknown. This study assessed the effects of diclofenac administration (10 mg/kg/day) on rats subjected to an exhaustive test, after six weeks of swimming training. Over the course of 10 days, three repeated swimming bouts were performed, and diclofenac or saline were administered once a day. Trained animals exhibited higher muscle citrate synthase and lower plasma creatinine kinase activities as compared to sedentary animals, wherein diclofenac had no impact. Training increased time to exhaustion, however, diclofenac blunted this effect. It also impaired the increase in plasma and liver interleukin-6 levels. The trained group exhibited augmented catalase, glutathione peroxidase, and glutathione reductase activities, and a higher ratio of reduced-to-oxidized glutathione in the liver. However, diclofenac treatment blunted all these effects. Systems biology analysis revealed a close relationship between diclofenac and liver catalase. These results confirmed that regular exercise induces inflammation and oxidative stress, which are crucial for tissue adaptations. Altogether, diclofenac treatment might be helpful in preventing pain and inflammation, but its use severely affects performance and tissue adaptation.